Create a Competitive Advantage for Karawo Small and Medium Enterprises - Ali Mohammad; Eka Zahra Solikahan (Universitas Pendidikan Ganesha, 2023)
SMEs contribute as support for the national economy, so SMEs need to be encouraged to increase their competitiveness by creating superior competitive advantages to have an impact not only on the domestic market but also on the global market. This study aims to analyze the effect of marketing strategy, innovation, financial knowledge, and demography on competitive advantage, besides that demography on innovation in Karawo SMEs in Gorontalo City. This study uses a sampling technique, namely purposive sampling with specific criteria so that the research sample is 78 Karawo SMEs that meet the criteria. The data collection method uses an online questionnaire. The method of data analysis is path analysis using SPSS version 20. The research results show that marketing strategy affects competitive advantage, innovation does not affect competitive advantage, financial knowledge does not affect competitive advantage, and demography affects competitive advantage. Demography affects innovation. Based on the results of this research, Karawo SMEs in Gorontalo City need to be able to innovate and increase their financial knowledge in order to create a competitive advantage. Therefore, it is possible to develop a model related to the factors that drive innovation based on the resource advantage theory for further research and the influence of financial literacy on competitive advantage.